Physical characteristics, management, and performance of newly recognized ‘Kathani cattle’ of Maharashtra state - BHAGAT, R L; DESHPANDE, V Y; SINGH, P K; TANTIA, M S (The Indian Journal of Animal Sciences, 2022)
Kathani cattle is not a registered cattle breed, consequently, these animals are categorized as non-descript animals in the Livestock Census of the Government of India. The population is about 10.51 lakh. Data of 9474 animals spread over 118 villages distributed in 13 tehsils of 3 districts (Chandrapur, Gadchiroli, and Gondia) from the Vidarbha region of eastern Maharashtra was collected under the survey, evaluation, and characterization network project of NBAGR, Karnal, during November 2017 to March 2020 and analyzed to document the physical characteristics, management, and performance of a new cattle breed available/found in Maharashtra state. Qualitative body part characters indicated that almost all animals had black coloured muzzle, eyelid, eyeball, hooves, tail switch. Biometry recorded included eight different body measurements in different age and sex groups. When compared with Gaolao, Kosali, Motu, and Ongole breeds of cattle from adjoining breeding tracts, molecular as well as phenotypic differentiation indicated separate genetic identities of the Kathani cattle. Nearly 96% Kathani cattle owners were found to provide housing to their animals and about 87% of respondents provided shelter during the night only while 7.4% provided both during day and night. Respondents (74.70%) cultivated fodder for their animals and general fodder in the area was leftover (after crop harvest) of paddy locally called Tanis, and soybeans, mung, wheat, cowpea, chickpea, pigeon pea, black gram locally called Kutar. The feed and fodder laboratory analysis revealed that Kathani animals were reared on very low nutritive value content like Tanis and different types of Kutars. Natural service was the preferred breeding method adopted by 94.8% and 5.2% of owners bred their animals through artificial insemination with the semen of exotic breed bulls. Kathani cattle keepers (61.9%) in the survey area experienced incidence of some of the contagious diseases and 72.55% of cattle holders vaccinatad their animals against these contagious diseases. The average age at first ejaculate for Kathani cattle males was 35.84±0.31 months, age at first calving was 54.86±0.05 months, calving interval was 486.85±0.51 days, daily milk yield was 0.55±0.01 litres, lactation length was 237.76±1.82 days and dry period noticed was 245.75±2.28 days. The study results will flag the way for the registration of the population as a new cattle breed and for the formulation of a breeding program for further improvement of this lesser-known cattle population.